THE IMAGE OF THE OTHER IN THE LETTERS OF IBN ABI AL-KHASAL AND ALUSI BETWEEN THE SOCIOLOGY OF PRAISE AND THE IDENTIFICATION OF THE SELF - Researcher. Mohsen Daadoush Abdel Reda, Asst. Prof. Dr. Sadiq Jaafar Abdul Hussein (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Ibn Abi embodied the other qualities to which he belongs in the political or social context in the form of praise, in the form of identification, whether the identification was conscious or conscious, as the other appeared in self-worth once in images of high status, once in images of affection, love and admiration, and another in images of mourning. The other with that sociology is a creative and human embodiment full of passionate emotion through which the identity of the self and the human experience emerged.Praise as a purpose that raises ideas and issues related to the social, political, and historical context, and is a creativity and human practice that identifies the writer in drawing the image of the praised. Their livelihood, the motives remain to him more than one factor, one time the motivation is psychological, and again it is social or economic.